"We Need to Redefine What We Mean by Winning": NAKASEC's Immigrant Justice Activism and Thinking Citizenship Otherwise. (4th May 2019) - Rubio, Elizabeth Hanna
ABSTRACT: The National Korean American Services and Education Consortium (NAKASEC) is becoming an increasingly influential player in national immigrant justice worlds. This article traces NAKASEC's evolving critique of legal recognition as the primary goal of immigrant justice work. Following organizers though a 22-day vigil at the White House, a 1700-mile bike tour, and the creation of a housing collective exclusively for illegalized people, I argue that NAKASEC's call to "re-define what we mean by winning" speaks to an emergent conceptualization of citizenship outside state inclusion. What does immigrant justice work look like when legalization is not its central goal?